IMPROVING STUDENTSâ COGNITIVE ABILITY AND LEARNING STYLES OF THE CONCEPT OF ENVIRONMENTAL POLLUTION BY USING SCIENCE COMICS - Riandi, Riandi; Mardiyah, Dieni Asma; Surakusumah, Wahyu (Faculty of Mathematics and Science Education, Universitas Pendidikan Indonesia, 2016)
This study investigated the use of science comics in improving studentsâ cognitive ability and learning styles on the concept of environmental pollution. First we develop science comics by using 4D model, then we evaluate studentsâ cognitive ability and learning styles after the developed science comics were implemented. Samples were seventh grade students in one of public schools in Bandung. Research instruments were multiple choice and essay test and questioner. Results suggested that the use of science comics increase studentsâ cognitive ability in all studentsâ class with average N-Gain of 0.6. In terms of learning style, students tend to be visual learners.